Oxidative Desulfurization of Simulated Diesel Fuel by Synthesized Tin Oxide Nano-Catalysts Support on Reduced Graphene Oxide - Mahmood, Qahtan A.; Abdulmajeed, Basma Abbas; Haldhar, Rajesh (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The modified Hummers method was applied to prepare graphene oxide (GO) from the graphite powder. Tin oxide nanoparticles with different loading (10-20 wt.%) supported on reduced graphene oxide were synthesized to evaluate the oxidative desulfurization efficiency. The catalyst was synthesized by the incipient wetness impregnation (IWI) technique. Different analysis methods like FT-IR, XRD, FESEM, AFM, and Brunauer-Emmett-Teller (BET) were utilized to characterize graphene oxide and catalysts. The XRD analysis showed that the average crystal size of graphene oxide was 6.05 nm. In addition, the FESEM results showed high metal oxide dispersions on the rGO. The EDX analysis shows the weight ratio of Sn is close to its theoretical weight. The reduction of metal oxide and (GO) has occurred in one step at temperatures of 400 °C for 2 hours. The performance of the catalysts for dibenzothiophene (DBT) removal using H2O2 as an oxidizing agent was determined under a range of different operating conditions. The results showed that the maximum desulfurization was 71.68% in the best conditions (DBT concentration = 385 ppm, time = 90 min, temperature = 60 oC, catalyst dosage = 0.04g, and amount of oxidant = 0.375 ml).